Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - 11.4 - Complex Numbers - Problem Set 11.4 - Page 493: 41



Work Step by Step

We multiply each term of the first complex number with the second complex number and then simplify: $(2+3i)(5+4i)$ =$2(5+4i)+3i(5+4i)$ =$10+8i+15i+12i^{2}$ =$10+23i+12i^{2}$ =$10+23i+12(-1)$ [as $i^{2}=-1$] =$10-12+23i$ =$-2+23i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.